2005
DOI: 10.1021/jo040281j
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Conversion of Biginelli 3,4-Dihydropyrimidin-2(1H)-one to Pyrimidines via PyBroP-Mediated Coupling

Abstract: An efficient two-step procedure is described to convert the Biginelli 3,4-dihydropyrimidin-2(1H)-one to various multifunctionalized pyrimidines via the Kappe dehydrogenation and a new mild PyBroP-mediated coupling with C, N, O, and S nucleophiles, which provides a readily accessible multifunctionalized pyrimidine template for diversity-oriented synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 33 publications
0
54
0
Order By: Relevance
“…44 This work appears to represent the first example of phosphonium-mediated carbon-nitrogen bond formation involving cyclic urea systems. The PyBroP-mediated amination likely occurs via the analogous phosphonium intermediate to 161, i.e.…”
Section: (1h-benzotriazol-1-yloxy)tripyrrolidinylphosphonium Hexafluomentioning
confidence: 87%
See 1 more Smart Citation
“…44 This work appears to represent the first example of phosphonium-mediated carbon-nitrogen bond formation involving cyclic urea systems. The PyBroP-mediated amination likely occurs via the analogous phosphonium intermediate to 161, i.e.…”
Section: (1h-benzotriazol-1-yloxy)tripyrrolidinylphosphonium Hexafluomentioning
confidence: 87%
“…products 37-43 (Scheme 11). 8 Further exploration of this reaction led to the important discovery that the amination of unprotected nucleosides, such as inosine (44) and 2¢-deoxyinosine (45), with the BOP reagent can be achieved directly without using protecting groups. This seemingly simple and efficient transformation eliminates two steps in the synthesis illustrated in Scheme 10 and was not reported before our publication in 2005.…”
Section: Scheme 11mentioning
confidence: 99%
“…25 Similarly, pyrimidines have been reported via palladium catalyzed Suzuki Sonogashira cross-coupling and Eschenmoser sulfide contraction reactions. 26,27 However, these useful approaches are multistep as well as involve expensive reagents and lack generality in many instances.…”
Section: E17mentioning
confidence: 99%
“…For a number of years, the versatility and efficiency of phosphonium-mediated coupling of tautomerizable heterocycles, [6] in particular nucleosides, has generated widespread attention. [7][8][9][10][11][12] Previous work by Lakshman et al [11] as well as our group [3] has shown that it is possible to convert certain protected guanosine derivatives to the corresponding O 6 -(benzotriazol-1-yl)guanosines using BOP and DBU. More specifically, TBS-protected guanosine was found to undergo this conversion in 65 % yield, while 2Ј,3Ј-isopropylidene-protected guanosine-5Ј-N-ethylcarboxamide gave a 95 % yield of the corresponding O 6 -(benzotriazol-1-yl) derivative.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study on the conversion of Biginelli 3,4-dihydropyrimidin-2(1H)-one to pyrimidines via PyBroP-mediated coupling, the choice of solvent was shown to have significant effect on the isolated yield. [6] Accordingly, we explored the reaction of guanosine with BOP and DBU in a range of solvents and the results are reported in Table 1. This reaction proceeded in low yield in a number of the solvents and guanosine's poor solubility was thought to be a major factor in these outcomes.…”
Section: Introductionmentioning
confidence: 99%